ANALISIS MASLAHAH MURSALAH TERHADAP LABEL HALAL PADA PRODUK BERDASARKAN UU NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Agung Setiono (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
Function halal label on the product under Law No. 8 of 1999 on Consumer Protection, kosher label, a product consumed goods can be categorized as dubious goods. So in this case the expected morality on the part of manufacturers to provide good protection to the consumer by the manufacturer in the form of voluntary labeling and lawful for the release of the product. Thus, consumers are becoming more comfortable and avoid worrying, given that the halal food for Muslims is principally because it relates to his religious beliefs. In maslahah mursalah in principle is an attempt in law specifies kemaslahatan community basing on the legal situation is not contained in the nash or ijma', there is also no denial of it explicitly. And can we assume that their kosher label on the product showed a positive impact or the benefits to all Muslims. In line with the above conclusion, so to guarantee kosher must memeperhatikan things above, can not be home produksen labeled kosher products even though they are already assured of halal production, before going through the testing and monitoring of body LPPOM, that this is done by LPPOM MUI. With the clarity of this label consumers can feel safe when consuming food..